The Protective Effects of In Vitro Cultivated Calculus Bovis on the Cerebral and Myocardial Cells in Hypoxic Mice - 蔡红娇 官阳 刘烈刚 姚平 裘法祖 (Journal of Huazhong University of Science and Technology. Medical sciences, 2007)
The protective effects of in vitro cultivated calculus bovis （ICCB） on the cerebral and myocardial cells in hypoxic mice and the mechanism were examined. In one group, mice were intragastrically （i.g.） given ICCB for 15 days and then they were subjected to acute cerebral ischemia by decapitation, and then the panting time was recorded. In the other group, 12 min after exposure to hypoxia, mice was administered the ICCB i.g. for 5 days, and then the blood serum and tissues of brain, heart, liver were harvested and examined for SOD, GSH-px and T-AOC activity and content of MDA. The tissues of brain and heart were observed electron-microscopically for ultrastructural changes. The corpus striatum and hippocampus of brain were collected and examined for content of dopamine （DA） and norepinephrine （NE）. The ultrastrural examination showed that the pathological change in brain and heart in the ICCB group was very slight, while abnormal changes in the control group were obviously more serious. ICCB significantly prolonged the panting time of the hypoxic mice （P〈0.001）, increased the activity of SOD, GSH-px, T-AOC in serum and tissues of brain, liver, heart and elevated the content of DA and NE. ICCB also pronouncedly reduced content of MDA in serum and tissues of brain, heart and liver. Significant differences in these parameters were noted between ICCB group and controls. It is concluded that ICCB can exert protective effect on the cells of brain and myocardium by enhancing the tolerance of the tissues to hypoxia and the body＇s ability to remove free radicals and regulating the neurotransmitters.